1990
DOI: 10.3109/03091909009015431
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of two laser Doppler blood flowmeters

Abstract: A new infrared laser Doppler blood flow instrument (Moor MBF3D) was evaluated using an in vitro model allowing measurements over a range of flow velocities and concentrations. The responses correlated well (r = 0.96, p less than 0.01) with those obtained simultaneously using a Perimed PF3 laser Doppler instrument. The different processing bandwidths of the instruments were investigated and the wideband mode of operation is recommended for flow measurements where there may be fast moving red blood cells (rbcs).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…Using 2 independent probes with online reading and analysis, matched with our histomorphological data, valid findings resulted. 26 When delayed plastic covering could not reconstitute cortical perfusion to sufficient levels (group B), early closure increased perfusion continuously to week 16, by which time near-normal values were reached (group A). 26 As stated by Smahel et al 24 a neoperiostal lining forms only after week 8 in cases of sufficient perfusion; this finding was confirmed by our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Using 2 independent probes with online reading and analysis, matched with our histomorphological data, valid findings resulted. 26 When delayed plastic covering could not reconstitute cortical perfusion to sufficient levels (group B), early closure increased perfusion continuously to week 16, by which time near-normal values were reached (group A). 26 As stated by Smahel et al 24 a neoperiostal lining forms only after week 8 in cases of sufficient perfusion; this finding was confirmed by our investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the processor by Nilsson [27] and also by Ahn et al [64] showed that this correction method works well till a volume fraction of around 1% is reached. A later study by Barnett et al [85] showed, however, that at higher perfusion rates this processor underestimates the flow. Petoukhova et al [86] did a comparative study of the output flow signal of two instruments, one with a linearizer and one without.…”
Section: Multiple Doppler Shifts: a Theoretical Limitationmentioning
confidence: 99%
“…This suggested that the linearization algorithm was not influencing the perfusion signal for a range of physiologically relevant flow values. The fact that the concentration signal was becoming saturated at higher flow values [86,87] and that the response of the power spectral density algorithm was extremely poor above concentrations of 0.2% volume fraction of RBCs [85], questions the usefulness of using the linearization algorithm under these conditions.…”
Section: Multiple Doppler Shifts: a Theoretical Limitationmentioning
confidence: 99%
“…Evaluation of the processor by Nilsson [27] and also by Ahn et al [64] showed that this correction method works well till a volume fraction of around 1%. But in a later study by Barnett et al [85] showed that at higher perfusion rates this processor under estimates the flow. Petoukhova et al…”
Section: Multiple Doppler Shifts; a Theoretical Limitationmentioning
confidence: 99%
“…This suggests that the linearization algorithm is not influencing the perfusion signal for a range physiologically relevant flow values. The fact that the concentration signal is getting saturated at higher flow values [86] and that the response of the power spectral density algorithm is extremely poor above concentrations of 0.2% volume fraction of RBC [85], questions the usefulness of using the linearization algorithm under these conditions.…”
Section: Multiple Doppler Shifts; a Theoretical Limitationmentioning
confidence: 99%